Pablo Picasso : Images de Picasso. - Clergue, Lucien; Villers, André; Musée Réattu Commanderie Sainte-Luce, Arles (Arles : Musée Réattu, 1991)
Beaton, Cecil ; Brihat, Denis ; Burri, René ; Capa, Robert ; Cartier-Bresson, Henri ; Clergue, Lucien ; Colomb, Denise ; Doisneau, Robert ; Duncan, David Douglas ; Glass, Douglas ; Gomes, Philippe ; Lartigue, Jacques-Henri ; List, Herbert ; Maar, Dora ; Man Ray ; Mili, Gion ; Miller, Lee ; Pic, Roger ; Picasso, Jacqueline ; Picasso, Pablo ; Pulham, Peter Rose ; Quinn, Edward ; Ronis, Willy ; Villers, André
Frans
Images de Picasso, Musée Réattu Commanderie Sainte-Luce, Arles, 8 février - 12 mai 1991
boek